Chemoenzymatic Synthesis of Substituted Azepanes by Sequential Biocatalytic Reduction and Organolithium-Mediated Rearrangement - Wojciech Zawodny; Sarah L. Montgomery; James R. Marshall; James Finnigan; Nicholas J. Turner; Jonathan Clayden (2018)
Enantioenriched 2-aryl azepanes and 2-arylbenzazepines were generated biocatalytically by asymmetric reductive amination using imine reductases or by deracemization using monoamine oxidases. The amines were converted to the corresponding N'-aryl ureas, which rearranged on treatment with base with stereospecific transfer of the aryl substituent to the 2-position of the heterocycle via a configurationally stable benzyllithium intermediate. The products are previously inaccessible enantioenriched 2,2-disubstituted azepanes and benzazepines.